Short-term clinical and serological follow-up with conventional and conformational anti-desmoglein antibodies in treatment-naïve and previously treated patients with pemphigus vulgaris after receiving rituximab - Hoorieh Alaeen, MD; Roja Toosi, MD, MPH; Hamidreza Mahmoudi, MD; Kamran Balighi, MD; Soheil Tavakolpour, MS; Amir Teimoupour, PhD; Maryam Daneshpazhooh, MD (Wolters Kluwer, 2019)
Background: Pemphigus vulgaris (PV) is a blistering, life-threatening autoimmune disease. Ethylenediaminetetraacetic acid (EDTA)-treated desmoglein (Dsg) enzyme-linked immunosorbent assay (ELISA) has recently been suggested to detect nonpathogenic antibodies. Rituximab (RTX) is now considered a first-line treatment for PV. Objective: The primary and secondary aims were to evaluate anti-Dsg and EDTA-treated anti-Dsg ELISA and clinical response before and 3 months after RTX in treatment-naïve and previously treated patients, respectively. In addition, we compared the short-term efficacy of RTX between these groups. Methods: Seventy-five patients with PV who received RTX (500 mg weekly for 4 weeks or 1000 mg 2 weeks apart) and prednisolone were followed for 3 months. Thirty-seven treatment-naïve newly diagnosed (group A) and 38 relapsed patients (group B) were included. Disease activity was scored with the Pemphigus Disease Area Index (PDAI). Clinical response was also assessed. Serum samples were collected at two points and examined for anti-Dsg1/3 and EDTA-treated anti-Dsg1/3. Conformational anti-Dsg values were calculated by subtracting EDTA-treated from conventional anti-Dsg values. Results: The correlation of conventional and conformational anti-Dsg values was perfect (correlation coefficient > 0.98; p < .001) at every time point for both anti-Dsgs. There was no difference with regard to PDAI and anti-Dsg values between the two groups at baseline. The frequency of responders was significantly higher in group A (100%) than in group B (89%; p = .006). Three patients relapsed, and five patients had persistent disease activity in group B. After 3 months, conventional and conformational anti-Dsg values were significantly higher in group B compared with group A (anti-Dsg3: p = .017 and .021, respectively; anti-Dsg1: p = .014 and .016, respectively). Total and scalp PDAI were significantly lower in group A than in group B (p = .042 and .016, respectively). Conclusion: EDTA-treated anti-Dsg ELISA had no added value. Using RTX as first-line treatment in patients with PV appears to be associated with better clinical response and immunologic profile than delayed treatment in the short term. Keywords: Pemphigus vulgaris, anti-desmoglein, ethylenediaminetetraacetic acid-treated desmoglein ELISA, rituximab, treatment, PDAI